Investigation of Chironomidae (Diptera) relationships using mitochondrial COI gene. (April 2015) - Sari, Adile; Duran, Mustafa; Sen, Alaattin; Bardakci, Fevzi
Abstract: Mitochondrial DNA sequences from cytochrome c oxidase subunit I ( COI ) were used to provide a phylogeny of the Chironomidae (Diptera) from Turkey. Data were obtained from 70 species of Chironomidae belonging to the genera Ablabesmyia, Chironomus, Cladotanytarsus, Conchapelopia, Cricotopus, Cryptochironomus, Dicrotendipes, Endochironomus, Eukiefferiella, Kiefferulus, Macropelopia, Micropsectra, Microtendipes, Paracladopelma, Paracricotopus, Paratanytarsus, Paratendipes, Paratrichocladius, Polypedilum, Psectrocladius, Psectrotanypus, Rheocricotopus, Tanytarsus, Thienemannimyia, Virgatanytarsus and Zavrelimyia . Neighbour-joining (NJ) and maximum likelihood (ML) analyses were used to identify the relationships among species. We confirmed monophyly of all sampled subfamilies and also tribes Chironomini, Tanytarsini, Macropelopiini and Pentaneurini, with the exception of subfamily Tanypodinae in ML analysis. However, in Chironomini, genus Chironomus, Cryptochironomus, Endochironomus and Paratendipes were monophyletic, while Polypedilum was not. Likewise, in Tanytarsini, genus Paratanytarsus and Cladotanytarsus were monophyletic, while Tanytarsus and Micropsectra were not. Also, in Macropelopiini and Pentaneurini, genus Macropelopia and Zavrelimyia were monophyletic. However, Ablabesmyia, genus of Pentaneurini, formed monophyletic group only in NJ analysis. In this study, we determined an unexpected inclusion of a Tanytarsus brundini individual into Micropsectra group. According to our pairwise distance analyses, the mean interspesific divergence was 19.4% for all species studied. Highlights: We provide highly sampled phylogeny estimate for Chironomidae from Turkey. A total of 171 individuals were used for molecular analyses. Mitochondrial COI sequences were used as phylogenetic marker. We confirmed monophyly of all sampled subfamilies and tribes in NJ analysis.